Hubungan Dukungan Keluarga terhadap Ketahanan Keluarga Masyarakat Pesisir di Laboratorium Psikologi Lapangan Kampung Bahari Nusantara TNI AL pada Suami - Pricilia Apriani Julianto; Arini Mifti Jayanti; Andy Sulistiono (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Family resilience is one of the factors that affects family support. Family resilience is about how the family plays the role of the family, faces problems, and manages conflict. To cope with this, family support is needed. Therefore, family support has a strong influence on family sustainability. The aim of this study is to test the correlation between family resilience and family support in the coastal community at the Psychology Laboratory of the village of Bahari Nusantara TNI AL. Subjects in this study are married coastal communities of 150 people. The research method used is quantitative correlation. The measurement is based on a family resilience scale using Walsh theory (2016) and a family support scale based on Friedman theory (2010). Data analysis shows a correlation with a spearman rank of 0.756 and a sig of 0.000 (p<0.05). Based on the data analysis, there is a positive relationship between family support and family sustainability. The higher the family support of the coastal people's husbands, the greater the family resilience of the family, and on the contrary, the lower the family's support, the less the family has.